THE EFFECTS OF FORM-FOCUSED INSTRUCTION ON LOWER-INTERMEDIATE EFL IRANIAN LEARNERS' GRAMMAR LEARNING - Somaye Ranjbar; Ehya Amalsaleh; Zahra Rastegar (Informascope, 2015)
One of the most controversial questions raised by classroom second language acquisition (SLA) researchers is whether and how to include grammar in second language (L2) classrooms. This study tried to investigate how the form-focused instruction affects lower-intermediate EFL Iranian learners' grammar learning. Based on an experimental data collection and analysis, the design of the study was a pre-test and post-test which dealt with 45 female participants at the pre-intermediate level. The pre-test was administered at the beginning of the course; then, the researchers observed two groups-- experimental (FFI) and control groups (traditional method). The researchers used an observation checklist which contained some items to investigate if the teacher used the related items in classes. Afterwards, the researchers provided the frequency of observation of teachers' operations which showed differences between the FFI and the traditional instruction. After observing the teaching sessions, we administered the same test as a post-test to both groups, the experimental and the control group. The data were analyzed through two types of t-tests, independent t-test and paired t-test. Key Words: form-focused Instruction (FFI); traditional Grammar Instruction.